ChemInform Abstract: Heterogeneous Catalysis by Gold. Issue 18 (11th April 2013) - Takei, Takashi; Akita, Tomoki; Nakamura, Isao; Fujitani, Tadahiro; Okumura, Misutaka; Okazaki, Kazuyuki; Huang, Jiahui; Ishida, Tamao; Haruta, Masatake
Abstract Review: 659 refs.